'No Country for Old Women': Female Aging in Bollywood. (October 2022) - Kumar, Saurav
In 2013, Sharmila Tagore 1 called Bollywood '[n]o country for old women'. 1 Like all older women, aging female actors of Bollywood too have experienced what Susan Sontag calls 'the double standard of aging': at older ages women are viewed as being too old to play central figures unlike men who play lead roles for a longer time. Aging reduces women's suitability as 'heroines' in the film industry. The article (a) provides a critical genealogy of female aging in the world of Indian cinema, which was born in the colonial era and (b) assesses the representation of older women in more recent Bollywood movies.